2017
DOI: 10.3390/rs9080832
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Annual Riparian Water Use Based on the Single-Satellite-Scene Approach

Abstract: Abstract:The accurate estimation of water use by groundwater-dependent riparian vegetation is of great importance to sustainable water resource management in arid/semi-arid regions. Remote sensing methods can be effective in this regard, as they capture the inherent spatial variability in riparian ecosystems. The single-satellite-scene (SSS) method uses a derivation of the Normalized Difference Vegetation Index (NDVI) from a single space-borne image during the peak growing season and minimal ground-based meteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Riparian water use continues to be an important area of research as large efforts are directed at controlling invasive riparian species (Bay & Sher, ; Khand et al, ) and competing sectors strain for already limited water availability. Tools that can provide accurate estimates of riparian ET at large spatial scales, such as SSEBop, can help inform water managers of the role of riparian consumptive water use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Riparian water use continues to be an important area of research as large efforts are directed at controlling invasive riparian species (Bay & Sher, ; Khand et al, ) and competing sectors strain for already limited water availability. Tools that can provide accurate estimates of riparian ET at large spatial scales, such as SSEBop, can help inform water managers of the role of riparian consumptive water use.…”
Section: Discussionmentioning
confidence: 99%
“…Senay et al () applied SSEBop using 31 years of Landsat archives in the south‐western United States and found that annual median riparian and agricultural ET can range from 1,500 to about 2,000 mm/year. Khand et al () showed the use of a single satellite scene method, with NDVI as a key input, to have accurate comparisons with a sophisticated model over appropriate spatial scales and subsequently used the single satellite scene method to estimate annual riparian ET for 23 years. Their average annual water use on the Colorado River in southern California is 748 mm, which is 62% less than our simulated average for all years at 1,949 mm (e.g., Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate estimates of regional scale ET are needed for sustainable water resource management, particularly for arid ecosystems due to competing demands for water resources among agricultural irrigation, public and domestic needs, industrial production, and ecological environments [4,5]. In recent decades, some empirical remotely sensed ET models have been developed [6][7][8][9][10][11][12][13][14] and their potential for regional scale ET estimation in arid ecosystems has been demonstrated [15][16][17][18][19][20][21][22][23][24][25][26]. These models extrapolate ET observed or estimated at the site scale to regional scale based on the empirical relationship constructed at the local site scale, which relates daily ET from the eddy covariance or Bowen ratio flux towers to vegetation indices (VIs) and meteorological data [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated the use of time series ET maps for ecological applications, such as capturing the progress of vegetation and wetland restoration [18], assessing the vulnerability of forest to fire and drought [19] and accounting water use from riparian vegetation and invasive species [20][21][22][23]. Remote sensing-based ET products have also been applied in improving the performances of hydrological models [24][25][26] and for climate studies to capture water feedbacks associated with seasonal cycles and soil moisture deficit at regional scales [27].…”
Section: Introductionmentioning
confidence: 99%